Chronic intermittent form of isovaleric aciduria in a 2-year-old boy - Jin Min Cho; Beom Hee Lee; Gu-Hwan Kim; Yoo-Mi Kim; Jin-Ho Choi; Han-Wook Yoo (Korean Pediatric Society, 2013)
Isovaleric aciduria (IVA) is caused by an autosomal recessive deficiency of isovaleryl-CoA dehydrogenase (IVD). IVA presents either in the neonatal period as an acute episode of fulminant metabolic acidosis, which may lead to coma or death, or later as a "chronic intermittent form" that is associated with developmental delays, with or without recurrent acidotic episodes during periods of stress, such as infections. Here, we report the case of a 2-year old boy with IVA who presented with the chronic intermittent form. He was admitted to Asan Medical Center Children's Hospital with recurrent vomiting. Metabolic acidosis, hyperammonemia, elevated serum lactate and isovalerylcarnitine levels, and markedly increased urine isovalerylglycine concentration were noted. Sequence analysis of the IVD gene in the patient revealed the novel compound mutations-a missense mutation, c.986T>C (p.Met329Thr) and a frameshift mutation, c.1083del (p.Ile361fs*11). Following stabilization during the acute phase, the patient has remained in a stable condition on a low-leucine diet.